Poly(ionic liquid)s with high density of nucleophile /electrophile for CO2 fixation to cyclic carbonates at mild conditions. (July 2019) - Xie, Yaqiang; Liang, Jun; Fu, Yawen; Lin, Ju; Wang, Hongtao; Tu, Song; Li, Jun
Graphical abstract: Multifunctional mesoporous poly(ionic liquid)s with high density of nucleophile/electrophile (bromide ions/zinc sites) were designed and prepared for atmospheric CO2 fixation at room temperature. Highlights: MPILs with high density of nucleophile/electrophile (Br–/Zn 2+ ) are prepared. Py-Im-6-Zn-5-SCD shows greatly enhanced CO2 fixing efficiency at mild conditions. Py-Im-6-Zn-5-SCD shows wide substrate scope for CO2 fixation. Structure & Activity Relationship is studied systematically. Abstract: The fixation of CO2 into high-value chemicals by multifunctional heterogeneous catalysts under mild conditions (atmospheric pressure, room temperature and additive-free) remains a great challenge. In this work, we report a series of multifunctional mesoporous poly(ionic liquid)s (PILs) in possession of high density of nucleophile/electrophile (bromide ions/zinc sites). They were synthesized from free-radical polymerization of imidazolium-based monomers with six ionic pairs (Im-6 ) and bipyridine (Py )-based monomers, followed by the efficient post-synthetic metallization and supercritical drying (SCD). All the obtained PILs with or without electrophile (zinc sites) were fully characterized to indicate their structural features of abundant mesopores, high surface areas, and large CO2 adsorption capacities. The catalytic performance of these PILs in CO2 fixation with propylene oxide into cyclic carbonate was systematically investigated under mild conditions. Among them, Py-Im-6-Zn-5-SCD shows greatly enhanced efficiency mainly due to the high density of active bromide ions/zinc sites and largest amount of effective acid sites in the abundant mesopore structures. Remarkably, various epoxide substrates could be effectively converted into cyclic carbonates byPy-Im-6-Zn-5-SCD even under mild conditions, with the catalyst being easily recycled.